Empowering Single Parents: Navigating Socio-Economic Challenges and Fostering Resilience in Family Well-being - Rees, Echave; Beeber, Scott Necşoi; Sampson, Russell; Lietz, Jeynes Pickett (Institute for Law and Economics Studies, 2023)
Single-parent households represent a diverse and growing family structure in contemporary society, often facing unique socio-economic challenges. This research seeks to comprehensively examine the role of single parents in meeting the socio-economic needs of their families, with a particular focus on the well-being of both parents and children. Through a mixed-methods approach encompassing quantitative surveys, qualitative interviews, and an extensive review of existing literature, this study aims to provide a nuanced understanding of the complexities and resilience demonstrated by single-parent households. Our findings reveal that single parents employ a variety of coping strategies, including meticulous financial planning, seeking education and job opportunities, and building robust support networks. These strategies are essential in navigating the financial stress, time constraints, and emotional strain often associated with single parenthood. Moreover, children in single-parent households often exhibit resilience through adaptive thinking, effective emotion regulation, and seeking support from trusted adults. Quantitative analyses indicate that academic achievement and reported stress levels in single-parent households may differ slightly from those in two-parent households. However, it is essential to consider that these outcomes are influenced by numerous factors beyond household structure, including income levels and parental involvement. Furthermore, our research underscores the significance of accessible support systems, including government assistance programs, community organizations, and family networks, in alleviating these challenges. In light of these findings, this research proposes a series of policy changes and interventions aimed at improving the socio-economic well-being of single-parent households. These include strengthening child support enforcement, expanding access to affordable childcare, increasing investments in affordable housing, and enhancing education and job training programs tailored to single parents' unique needs. In conclusion, the socio-economic well-being of single-parent households is a multifaceted and vital concern in contemporary society. By recognizing the diverse strengths and challenges these families face and implementing inclusive policies and support systems, we can empower single parents and their children to thrive. This research contributes to a deeper understanding of single-parent dynamics and resilience while offering actionable recommendations to enhance their socio-economic prospects and foster a more inclusive future for all families.